Integrating Artificial Urban Wetlands Into Communities: A Pathway to Carbon Zero? - Rogerson, Robert J.; Horgan, Donagh; Roberts, Jennifer J. (Frontiers in Built Environment, 2021)
In their natural state, wetland ecosystems provide an optimum natural environment for the sequestration and long-term storage of carbon dioxide (CO2) from the atmosphere. The loss of wetlands under advancing urbanization not only diminishes this capacity for storage, but increases methane and greenhouse gases as the land is disturbed. Nevertheless, there is growing scientific interest in using artificial or constructed wetlands as a way to mitigate the impact of global climate change. To date, most attention has focused on the use of urban wetlands for water management. Using a potential integrated urban wetland site in Glasgow as a case study, this paper critically examines how artificial urban wetlands can contribute to urban net zero targets in terms of their ability for carbon sequestration, and as part of sustainability initiatives more broadly. We find there are several barriers to implementing artificial urban wetlands for carbon drawdown alone, in particular regarding land ownership constraints, uncertainties in capture efficacy and capture quantitation, and eligibility for market-based crediting schemes. These issues make it currently challenging for the carbon reduction contribution of urban wetlands to be quantified and, say, certified to generate revenue to communities through market-based carbon crediting. However, if integrated within wider community-based sustainability initiatives, artificial urban wetlands can support multiple dimensions of sustainability, creating or supporting value far beyond water management and carbon sequestration objectives. Potential co-benefits range from areas such as health and wellbeing, biodiversity, education, food security, behavioural changes and social care. Our findings show that for these co-benefits to be identified, maximised and realised, a place-based approach to urban wetland development must be adopted, engaging stakeholders from the project outset to define and facilitate collaboration towards shared outcomes for society, community and environment. These findings will be relevant to any urban infrastructure development seeking to meet sustainability goals beyond carbon capture.